IMPROVING THE QUALITY OF ACADEMIC SUPPPORT SERVICES TO CONTRIBUTE TO THE INNOVATION OF HIGHER EDUCATION - Ly Ngoc Yen Nhi* , Nguyen Thi Tuong Vi, Pham Yen Linh, Pham Hoang Bao Vy, Pham Nguyen Ngoc Thu (Tạp chí Khoa học, 2024)
Today, academic support services have become increasingly important to universities because they can help students develop knowledge and skills to more easily achieve success during university studies, thereby contributing to developing the reputation of training institutions. Therefore, many universities around the world have increasingly focused on developing academic support services. In Vietnam, academic support services at universities have begun to receive attention but have not really reached the quality commensurate with learners' requirements. Through understanding the theoretical basis of the quality of academic support services in higher education, as well as analyzing the current status of the quality of academic support services at a number of domestic and world universities, the study proposes a number of recommendations on improving the quality of academic support services to contribute to the innovation of Vietnamese higher education.